Pengaruh Motivasi dan Kepuasan Kerja terhadap Kualitas Pelayanan: Survey pada Karyawan BTN Kantor Cabang Syariah Kota Bekasi - Ikbal Gamawardi Pernanu; Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
This study aims to identify and analyze the influence of work motivation and job satisfaction on the quality of service employees BTN Syariah Bekasi branch office. The entire population was 60 employees, while the samples used in this study were 13 respondents, the sampling technique by purposive sampling technique. The method used in this research is quantitative analysis with multiple linear regression analysis two predictors with a significance level α = 5% by using SPSS version 16.0 for Windows. Results of the research is a significant difference between the variable partial motivation to work on service quality for T1 count = 4.302> table T = 2, 201. While there is no significant effect partially between the independent variable on the dependent variable of job satisfaction for service quality T2 count = 0, 535 <T table = 2, 201. There is a significant influence simultaneously between the independent variable motivation and job satisfaction on the dependent variable service quality obtained by F count = 10, 090> F table = 4, 10. Thus the independent variable motivation and job satisfaction have a significant effect simultaneously on the dependent variable service quality.